Association between Stress Hyperglycemia Ratio and In-Hospital Mortality in Patients with Sepsis [Letter] - Hao Y (Journal of Inflammation Research)
Yu Hao School of Graduate, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150006, People’s Republic of ChinaCorrespondence: Yu Hao, School of Graduate, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150006, People’s Republic of China, Email tg2605330019@163.com